Adapting to the dark : reflections of local culture in recent New Zealand horror cinema : a thesis in partial fulfilment of the requirements for the degree of Master of Philosophy in Media Studies at Massey Universit - Ryan, Paolo; Ryan, Paolo (Massey University, 2011)
The use of Hollywood genres to package our films for overseas consumption has been an historic feature of the New Zealand film industry. The horror genre has been an important platform for many local film directors, equipping them with sufficient technical skills to create a „calling card‟ for entry into Hollywood. But in working with the genre locally, these directors have introduced variations that are culturally specific to New Zealand, a process of assimilation known as „indigenisation.‟ This relies upon a shared understanding of ethnic and cultural identity, and in some cases has given rise to a perceptible New Zealand film brand. While government policy may assist to promote certain features in the interest of creating and sustaining a commercially viable „National Cinema,‟ real and sometimes problematic aspects of our contemporary society, such as the increasing influence of Pacific Island culture or the position of Maori in respect of the mainstream may be downplayed or omitted altogether. This thesis examines the extent to which indigenisation has occurred in some recent examples of New Zealand horror films. It considers the theory of National Cinema and the influence of government policy on cinema practice, and examines the image of the nation that has been constructed thus far. It also outlines the theory of genres and how they are interpreted and transformed over time, and identifies the distinguishing characteristics of the horror genre. The analysis of the case studies, which include recent examples of mainstream and Pacific Island-influenced films, addresses the question of how the horror genre is culturally inflected and what images of the nation prevail. It concludes that our films may not even admit alternative local constructs of the nation, and that as we become more inundated in the streams of foreign influence and capital, there is an increasing amount of attention being given to how identity and culture is formed rather than to describing the specific cultural features of a given nation. This is reflected in the rise of generic hybridity and multi-vocalic texts, whose voices may simply express a desire to navigate the cross-currents of global consumer culture.
Keywords: New Zealand movies; Cultural identity; National cinema; Indigenisation